Posing Problems, Setting Up Situations and Asking Questions of Problem-Solving Menus Activities: Towards the Steps in Helping Students Interact with One or More Mathematical Ideas - Saldo, Vincent (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship among posing problems, setting up situations, and asking questions through problem-solving menu activities in helping students interact with mathematical ideas. Specifically, it assessed teachers’ implementation of these instructional components, determined whether significant differences existed according to respondents’ demographic profiles, and examined the relationships among the variables. The study was anchored on experiential learning and constructivist perspectives, emphasizing active student participation and meaningful knowledge construction in mathematics instruction. A quantitative research approach employing comparative and correlational research designs was utilized. The respondents were randomly selected Master Teachers from secondary schools in the Province of Cavite. Data were collected using a researcher-made questionnaire that underwent expert validation and reliability testing before administration. The gathered data were analyzed using descriptive statistics, independent t-test, one-way analysis of variance (ANOVA), and Pearson’s correlation coefficient. The findings revealed that teachers demonstrated evident practices in posing problems, setting up situations, and asking questions through problem-solving menu activities, indicating consistent implementation of learner-centered instructional strategies. No significant differences were found in these practices when respondents were grouped according to age, years in service, educational attainment, position or rank, and grade level assignment. However, significant positive relationships were identified among posing problems, setting up situations, and asking questions, suggesting that these instructional components complement one another in promoting effective mathematics instruction and students’ problem-solving abilities. The study concludes that integrating problem-posing and problem-solving menu activities strengthens meaningful mathematics learning by fostering critical thinking, analytical reasoning, and active student engagement. It recommends continuous professional development, collaborative instructional practices, and supportive learning environments to further enhance teachers’ implementation of these strategies. The study supports Sustainable Development Goal 4 (Quality Education) by promoting effective and learner-centered mathematics instruction and contributes to educational sustainability through evidence-based practices that strengthen teaching quality and meaningful learning outcomes.